Performance Analysis of Fifth-Semester Physics Education: Assessing an Online Pascal Compiler in the Department of Mathematics and Natural Sciences Education at University of Mataram - Taufik, Muhammad; Ayub, Syahrial (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study evaluates the integration of online Pascal compilers in undergraduate physics education at the University of Mataram, focusing on its impact on students' programming skills. Over one semester, three classes (A, B, and C) of physics education students from the Department of Mathematics and Natural Sciences Education (PMIPA), Faculty of Teacher Training and Education (FKIP), University of Mataram, participated in lectures, discussions, and practical exercises using the GDB Online Pascal Compiler. Course content included Pascal fundamentals, arrays, matrices, and applications in physics, evaluated through assignments, mid-semester, and final exams. Quantitative analysis of student performance data revealed significant differences in mean scores and variability among the classes, with Class A achieving the highest average score and Class C exhibiting the greatest variability. Statistical tests confirmed that performance data for all classes deviated significantly from normal distribution, necessitating non-parametric tests. The Mann-Whitney U test indicated no statistically significant differences in median scores between class A vs. class B, class A vs. class C, and class B vs. class C, suggesting consistent performance outcomes across classes post-course. These findings underscore the potential of the online Pascal compiler in enhancing students' programming skills within the context of physics education.